In the lion's den : the life of Oswald Rufeisen - Tec, Nechama 1931- (Oxford Univ. Press, 1990)
A moving biography of Oswald Rufeisen, a Jew who passed as a Christian in occupied Poland, worked as a translator for the German police, and risked his life to save hundreds from the Nazis. Denounced, he escaped and found shelter in a convent, where he became a Catholic and later a priest and monk.